Usos do passado Leitura da História na perspectiva jornalística de Laurentino Gomes no livro 1808 - Bezerril, Simone da Silva (2013)
Through the growing number of works of historical content written by journalists, accompanied by a significant rate of sales in the Brazilian publishing market, this paper proposes a case study having as object the book 1808 - As a mad queen, a prince and a nervous corrupt court deceived Napoleon and changed the history of Portugal and Brazil, the journalist Laurentino Gomes. As in the production of this type parameter are historiographical works and procedures aimed to understand how an author who has no historical training develops your "mechanics" of production, ie, a method of writing, the "handle" works of historians and extract these elements to the disclosure of their interpretations and construction of his narrative about the past, whose intention goes through the configuration of a palatable and attractive text about what happened. It is perceived that such production provides a fine line between history and journalism, to use elements from both camps. In this dissertation, raised the hypothesis that the work of Laurentino Gomes can be understood as a product of historical culture, when considering that revisiting the past is not an exclusivity of the historian. Although books like this said journalist contributing to the popularization of historical knowledge, not always depict plausibly, ie without anachronisms. Appears that 1808, to be "made-up" as a work of history, although its author emphasizes that this is journalism, brings the main epistemological implication of the fact to be taken by society as historiographical reference, as if the "make history "in the sense of institutionalized and metodizado knowledge was not restricted to the production of professional métier. Therefore, the practice of writing about the past can t historiographical legitimacy, but it is legitimized by the market-intakes and the social practices of reading, inserted in the cultural industry "past as a commodity."